Psychological Availability between Self-Initiated Expatriates and Host Country Nationals during Their Adjustment: The Moderating Role of Supportive Supervisor Relations - Jannesari, Milad; Wang, Zhongming; McCall, Jacob; Zheng, Boyang (Frontiers in Psychology, 2017)
This research examined the role of psychological availability as a means of psychological engagement between self-initiated expatriates (SIEs) and their host-country nationals (HCNs) colleagues during their work and interaction adjustment. To reveal this process, this study presented the concept of psychological availability, which refers to an individual’s belief that they are physically, cognitively, and emotionally ready or confident to engage the self with their colleagues, as a mediator between proactive personality and adjustment. Also, it investigated the relationship between proactive personality and psychological availability and how it was moderated by supportive supervisor relations. We hypothesized, this relationship would be weakened/strengthened when SIEs and HCNs received low/high level of support from their supervisor. This study was conducted as a quantitative study, data was used from 342 SIEs and 342 HCNs working in mainland China. Our finding supported the hypothesis that psychological availability mediated the relationship between proactive personality and their adjustment to an international work environment; in addition, the relationship between proactive personality and psychological availability would be stronger when the level of superiors relations support is high between SIEs and HCNs. This study demonstrated the value of proactive personality as an antecedent effect and supportive supervisor relations as a moderating effect, and investigated how these factors can lead to a sense of psychological availability and boost psychological engagement between SIEs and HCNs in order to improve the adjustment between them.